Artysta na obrzeżach świata, czyli wszyscy jesteśmy Odyseuszami. Kilka refleksji ogólnych w nawiązaniu do Cycerona, Owidiusza i Seneki - Wesołowska, Elżbieta (Studia Europaea Gnesnensia, 2010)
Th e paper discusses three grand personalities of antiquity: Cicero, Ovid and Seneca in the circumstances of their exile, Th eir attitudes to the punishment received (whose severity varied) were diverse. Nevertheless, all they left a trace in the shape of literary works and letters. Upon reading, one discovers ambiguous attitudes towards their personal misfortunes. Finally, the situation of the exiles and their return may be compared with the archetypal fi gure of Odysseus.